FOAM (Functional Ontology Assignments for Metagenomes): a Hidden Markov Model (HMM) database with environmental focus - Prestat, Emmanuel; David, Maude M.; Hultman, Jenni; Taş, Neslihan; Lamendella, Regina; Dvornik, Jill; Mackelprang, Rachel; Myrold, David D.; Jumpponen, Ari M.; Tringe, Susannah G.; Holman, Elizabeth; Mavromatis, Konstantinos; et al. (My University, 2015)
A new functional gene database, FOAM (Functional Ontology Assignments for Metagenomes), was developed to screen environmental metagenomic sequence datasets. FOAM provides a new functional ontology dedicated to classify gene functions relevant to environmental microorganisms based on Hidden Markov Models (HMMs). Sets of aligned protein sequences (i.e. ‘profiles’) were tailored to a large group of target KEGG Orthologs (KOs) from which HMMs were trained. The alignments were checked and curated to make them specific to the targeted KO. Within this process, sequence profiles were enriched with the most abundant sequences available to maximize the yield of accurate classifier models. An associated functional ontology was built to describe the functional groups and hierarchy. FOAM allows the user to select the target search space before HMM-based comparison steps and to easily organize the results into different functional categories and subcategories. FOAM is publicly available at http://portal.nersc.gov/project/m1317/FOAM/.
Keywords: Gene database; Metagenomes; Functional ontology; Hidden Markov Models